Revolutionizing Talent Acquisition in Indonesia’s E-Commerce Industry: The Transformative Impact of AI and Machine Learning - Rayyan, Mohammad; Sharifah, Nakayenga; Kuswati, Rini (Journal of Humanities and Social Sciences Studies, 2024)
This research explores the impact of Artificial Intelligence (AI) and Machine Learning (ML) on talent acquisition within Indonesia’s growing e-commerce sector. While acknowledging the transformative potential of these technologies, the study uncovers significant challenges in their integration into existing talent acquisition processes. These challenges include issues related to data quality, model accuracy, and system adaptability. The study emphasizes the difficulty of acquiring talent with expertise in AI and ML, given the increasing demand for skilled workers in the e-commerce boom. It explores strategies employed by companies to address this talent gap, such as upskilling existing staff and seeking external expertise. The research provides a nuanced understanding of AI and ML applications in the Indonesian e-commerce landscape, highlighting both benefits and obstacles. The insights derived from the study aim to offer actionable guidance for e-commerce firms, HR professionals, and researchers navigating the evolving landscape of AI, ML, and talent acquisition in Indonesia’s digital marketplace.